Gene expression profiling of substantia nigra dopamine neurons: further insights into Parkinson's disease pathology - Simunovic, Filip; Yi, Ming; Wang, Yulei; Macey, Laurel; Brown, Lauren T.; Krichevsky, Anna M.; Andersen, Susan L.; Stephens, Robert M.; Benes, Francine M.; Sonntag, Kai C. (Brain (London, England : 1878), 2009)
Parkinson's disease is caused by a progressive loss of the midbrain dopamine (DA) neurons in the substantia nigra pars compacta. Although the main cause of Parkinson's disease remains unknown, there is increasing evidence that it is a complex disorder caused by a combination of genetic and environmental factors, which affect key signalling pathways in substantia nigra DA neurons. Insights into pathogenesis of Parkinson's disease stem from in vitro and in vivo models and from postmortem analyses. Recent technological developments have added a new dimension to this research by determining gene expression profiles using high throughput microarray assays. However, many of the studies reported to date were based on whole midbrain dissections, which included cells other than DA neurons. Here, we have used laser microdissection to isolate single DA neurons from the substantia nigra pars compacta of controls and subjects with idiopathic Parkinson's disease matched for age and postmortem interval followed by microarrays to analyse gene expression profiling. Our data confirm a dysregulation of several functional groups of genes involved in the Parkinson's disease pathogenesis. In particular, we found prominent down-regulation of members of the PARK gene family and dysregulation of multiple genes associated with programmed cell death and survival. In addition, genes for neurotransmitter and ion channel receptors were also deregulated, supporting the view that alterations in electrical activity might influence DA neuron function. Our data provide a ‘molecular fingerprint identity’ of late–stage Parkinson's disease DA neurons that will advance our understanding of the molecular pathology of this disease.